Proper Names in Translations for Children: Alice in Wonderland as a Case in Point - Nord, Christiane (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2003)
AbstractDrawing on a corpus of eight translations of Lewis Carroll’s Alice in Wonderland into five languages (German, French, Spanish, Brazilian Portuguese, Italian), the paper discusses the forms and functions of proper names in children’s books and some aspects of their translation. In Alice in Wonderland, we find three basic types of proper names: names explicitly referring to the real world of author and original addressees (e.g., Alice, her cat Dinah, historical figures like William the Conqueror), names implicitly referring to the real world of author and original addressees (e.g., Elsie, Lacie and Tillie, referring to the three Liddell sisters Lorina Charlotte, Alice and Edith Mathilda), and names referring to fictitious characters. An important function of proper names in fiction is to indicate in which culture the plot is set. It will be shown that the eight translators use various strategies to deal with proper names and that these strategies entail different communicative effects for the respective audiences.